Model Peningkatan Minat Masyarakat terhadap Madrasah Ibtidiyah di Jawa Tengah - Sofanudin, Aji (Nadwa, 2012)
This study aims to determine the model of the increase in the public interest to send their children to the MI MaArif Grabag 1 Magelang. The result is: that the interest of the public to send their children to madrassas is relatively high as indicated by the number of parents who participated guardian to register sons and daughters to the madrassa. Management of educational institutions include the flagship program and habituation. Model increase public interest to send their children at the school by offering excellent programs, familiarize noble character, academic achievement and superior non-academic achievements and establish intense cooperation with various parties.